Is It Scaly Anteater or Bat A Real Origin of The 2019-Novel CoV: A Probable Hypothesis? - Ali, Salar; Hama-Soor, Taib; Babakir-Mina, Muhammed; Dimonte, Salvatore; Greco, Francesco (Kurdistan Journal of Applied Research, 2020)
Today, the emerging of the new coronavirus 2019nCoV possesses a global health problem and little is known about its origin. In the current investigation, an evolutionary and molecular epidemiological analysis have provided of this new emerged virus. The phylogenetic trees for animal coronaviruses with the novel coronavirus-2019 have been created using a number of available complete protein sequences of envelope (E), membrane (M), nucleocapsid (N) and spike (S) proteins. The phylogenetic trees analysis illustrated that 2019nCoV in all four proteins are very closely related with coronaviruses isolated from Pangolin (scaly anteater) and Bat-SARS-like-coronavirses because all of them are clustered in the same clade. Whereas, the 2019nCoV is less closely related to coronavirses isolated from Rousettus bat (fruit bat) and MERS coronaviruses isolated from camel because they are gathered in the same clade only in two of the four studied proteins, nucleocapsid (N) and spike (S). In the conclusion, the new 2019nCoV is more likely to be originated from Bat-SARS-like-coronaviruses or/and coronavirus isolated from Pangolin after adaptation and evolution in the human hosts. Because of the number of infected cases to date indicates a very quick human-to-human transmission. Thus, necessitates a very rapid active surveillance using accurate method to find the original host where the 2019nCoV emerged. This will help in further understanding and creating a better approach to control the spread of SARS-CoV-2 outbreak.